2014
DOI: 10.4269/ajtmh.13-0496
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Young Children with Inherited Blood Disorders in Western Kenya

Abstract: To determine the association between a range of inherited blood disorders and indicators of poor nutrition, we analyzed data from a population-based, cross-sectional survey of 882 children 6–35 months of age in western Kenya. Of children with valid measurements, 71.7% were anemic (hemoglobin < 11 g/dL), 19.1% had ferritin levels < 12 μg/L, and 30.9% had retinol binding protein (RBP) levels < 0.7 μmol/L. Unadjusted analyses showed that compared with normal children, homozygous α+-thalassemia individuals had a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 39 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…In a previous trial in the same area as the present study, α + -thalassaemia occurred in 48.8% of pregnant women (heterozygotes: 41.3%; homozygotes: 7.5%), but there was no evidence that it was associated with ZPP [ 4 ]. In a nearby area, the prevalence of sickle cell trait and sickle cell disease in preschool children was 17.1% and 1.6%, respectively; genotypes indicating G6PD deficiency occurred in 8.2% of males and 6.8% of children overall, whilst the prevalence of haptoglobin 2–2 genotype was 20.4% [ 17 , 18 ] A study in Gambian children aged 2–6 years, however, failed to find an association between haptoglobin genotype and ZPP [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous trial in the same area as the present study, α + -thalassaemia occurred in 48.8% of pregnant women (heterozygotes: 41.3%; homozygotes: 7.5%), but there was no evidence that it was associated with ZPP [ 4 ]. In a nearby area, the prevalence of sickle cell trait and sickle cell disease in preschool children was 17.1% and 1.6%, respectively; genotypes indicating G6PD deficiency occurred in 8.2% of males and 6.8% of children overall, whilst the prevalence of haptoglobin 2–2 genotype was 20.4% [ 17 , 18 ] A study in Gambian children aged 2–6 years, however, failed to find an association between haptoglobin genotype and ZPP [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information on SCD has mainly been reported among US population, India and Jamaica, with less information in Africa where the gene is highly predominant. Although some studies [6,7] have reported on nutritional status of children with SCD in parts of Africa, there has been paucity of studies designed to identify the dietary intake of children with SCD in Ghana. A study in Ghana [8] reported on high prevalence of malnutrition (61.3%) among children with SCD but did not consider their dietary intake.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study that involved young patients aged 6-35 months showed no association with wasting, stunting, or underweight status. [34] A study of 233 children aged 2-17 years with SCD in Lagos, Nigeria found that the factor most signi cantly associated with both wasting and stunting was older age.…”
Section: Resultsmentioning
confidence: 99%
“…The second most common group of studies identi ed involved assessment of biomarkers from serum samples for macronutrients or micronutrients. Most studies were conducted in Nigeria (17/22, 77%); other studies took place in DRC, [49] Tanzania, [25] Egypt, [50] Kenya, [34] and Malawi. [51] Nutritional parameters measured included proteins/amino acids, fatty acids, vitamins, and minerals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation